Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.26 First order constant coefficients

In MATH101 slide 3.17, you saw that the general solution for the differential equation

dydx-ky=0\frac{dy}{dx}-ky=0

is y=Aekxy=Ae^{kx} where AA is a constant. More generally, let us consider the equation dydx-ky=q(x)\frac{dy}{dx}-ky=q(x) for a function q(x)q(x). This is a first-order linear equation, so we can solve it using the method on slides 6.19-20. In this case p(x)=-k,p(x)={-k,} so the integrating factor I(x)=e-kx.I(x)={e^{-kx}.}

Multiplying through by I(x)I(x), we obtain the integrable differential equation

ddx(ye-kx)=q(x)e-kx\frac{d}{dx}\left(ye^{-kx}\right)=q(x)e^{-kx}

which we integrate, to obtain ye-kx=g(x)+cye^{-kx}=g(x)+c where g(x)=q(x)e-kxg^{\prime}(x)=q(x)e^{-kx} and cc is a constant. Multiplying through by ekxe^{kx}, we get the general solution:

y=g(x)ekx+cekx.y=g(x)e^{kx}+ce^{kx}.